(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This was a descriptive, correlational study designed to evaluate the capacity to direct attention (CDA) of the nurse and to verify an association between the CDA and attention demand situations. For data collection the instruments used were: the Attentional Function Index and the Directed Attention Demands. The participants were 169 nurses of a teaching hospital in the State of São Paulo. The mean perception of performance or CDA was 60.4 which differed between the variables: unit of work (p=0.013), work hours (p=0.044), presence of health problems (p=0.026) and problems of a psychological nature (p=0.005). There was a negative association between the situations of demand and CDA (r = - 0.294, p